Assessment of dead-space ventilation in patients with acute respiratory distress syndrome: a prospective observational study. Issue 1 (December 2016) - Doorduin, Jonne; Nollet, Joeke; Vugts, Manon; Roesthuis, Lisanne; Akankan, Ferdi; van der Hoeven, Johannes; van Hees, Hieronymus; Heunks, Leo
Abstract Background Physiological dead space (VD /VT ) represents the fraction of ventilation not participating in gas exchange. In patients with acute respiratory distress syndrome (ARDS), VD /VT has prognostic value and can be used to guide ventilator settings. However, VD /VT is rarely calculated in clinical practice, because its measurement is perceived as challenging. Recently, a novel technique to calculate partial pressure of carbon dioxide in alveolar air (PACO2 ) using volumetric capnography (VCap) was validated. The purpose of the present study was to evaluate how VCap and other available techniques to measure PACO2 and partial pressure of carbon dioxide in mixed expired air (PeCO2 ) affect calculated VD /VT . Methods In a prospective, observational study, 15 post-cardiac surgery patients and 15 patients with ARDS were included. PACO2 was measured using VCap to calculate Bohr dead space or substituted with partial pressure of carbon dioxide in arterial blood (PaCO2 ) to calculate the Enghoff modification. PeCO2 was measured in expired air using three techniques: Douglas bag (DBag), indirect calorimetry (InCal), and VCap. Subsequently, VD /VT was calculated using four methods: Enghoff-DBag, Enghoff-InCal, Enghoff-VCap, and Bohr-VCap. Results PaCO2 was higher than PACO2, particularly in patients with ARDS (post-cardiac surgery PACO2  = 4.3 ± 0.6 kPa vs. PaCO2  = 5.2 ± 0.5 kPa, P  < 0.05; ARDS PACO2  = 3.9 ± 0.8 kPa vs. PaCO2  = 6.9 ± 1.7 kPa, P  < 0.05). There was good agreement in PeCO2 calculated with DBag vs. VCap (post-cardiac surgery bias = 0.04 ± 0.19 kPa; ARDS bias = 0.03 ± 0.27 kPa) and relatively low agreement with DBag vs. InCal (post-cardiac surgery bias = −1.17 ± 0.50 kPa; ARDS mean bias = −0.15 ± 0.53 kPa). These differences strongly affected calculated VD /VT . For example, in patients with ARDS, VD /VT calculated with Enghoff-InCal was much higher than Bohr-VCap (VD /VT Enghoff-InCal  = 66 ± 10 % vs. VD /VT Bohr-VCap  = 45 ± 7 %;P  < 0.05). Conclusions Different techniques to measure PACO2 and PeCO2 result in clinically relevant mean and individual differences in calculated VD /VT, particularly in patients with ARDS. Volumetric capnography is a promising technique to calculate true Bohr dead space. Our results demonstrate the challenges clinicians face in interpreting an apparently simple measurement such as VD /VT .